A comparative analysis of a white-roof installation during a New Zealand autumn and winter. Issue 1 (2nd January 2016) - Taylor, Adam P. R.
Abstract: It has been asserted that a white roof reflects the sun's rays back into space, reducing the heat absorbed into the structure beneath it and therefore reducing the cooling requirements of the occupied space. This paper presents comparative field data on structurally identical buildings with an installation of a painted white (Titania) iron roof compared to the neighbouring existing control (red) iron roof for autumn and winter. It is shown that there were significant variances in roof surface and roof cavity temperatures between the building with the white roof and the building with the red roof, and that the occupied rooms in the two near-identical buildings showed very similar temperatures during the cooler parts of the day. It is suggested that the roof colour of a ceiling-insulated structure has very little impact on the temperature of the occupied and insulated space, but that during the hotter parts of the day there can be up to a 10°C temperature differential in the roof. From this preliminary data of two neighbouring near-identical buildings, it appears that white roofs do help to reduce the internal temperature of a structure during hotter periods, even when that structure is insulated with ceiling batts, and does not impinge on the internal temperature of structures during cooler periods.